An anti-fascist model to be found: an experience from the Popular Theater School (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
The article is an effort to discuss an experience of creating a Brechtian theater model on the theme of fascism by the Escola de Teatro Popular (ETP). To do so, (1) we present what the ETP is, and then (2) what the ETP understands as a model for Brecht. Next, (3) the theme of fascism is discussed, along with (4) how Brecht's biography and works engaged with this theme, especially considering the period of German Nazism from the 1930s until the end of World War II. This provides the foundation to finally present the model on fascism currently being developed by the Escola de Teatro Popular. The theme is highly relevant, considering the rise of the fascist far-right, which has required the ETP to find ways to represent the form of fascism on stage.
Keywords: fascim; Brecht; models; school of Popular Theater